On (the lack of) responsibility in EFL education: A tale of the private sector - Weisi, Hiwa; Rahimi, Rana (LPMPP Universitas Negeri Yogyakarta, 2026)
Effective communication is a crucial aspect of language learning, especially in the context of English as a foreign language (EFL) education. Such skills are essential for students to develop the ability to express themselves fluently and accurately in real-life communication. The present study aimed to explore EFL teachers' sense of responsibility in the private sector of Iran in teaching communicative skills and to demonstrate strategies to improve responsibility in this area among teachers. Data were collected through narrative frames and individual interviews with a sample of EFL teachers in private institutes. The findings suggested that several factors may contribute to teachers' lack of responsibility in teaching communicative skills, including low payments, a lack of emphasis on communicative skills in curricula and course books, and learners' demotivation. These factors result in a cycle of underperformance and demotivation, which negatively impact teachers' motivation to effectively teach communicative skills. The study highlights the importance of addressing these issues and empowering EFL teachers to take ownership of their students' language learning journeys and opens the door to new possibilities. Implications are discussed in light of the research findings.